2017
DOI: 10.1038/s41598-017-13373-5
|View full text |Cite
|
Sign up to set email alerts
|

Priming with FGF2 stimulates human dental pulp cells to promote axonal regeneration and locomotor function recovery after spinal cord injury

Abstract: Human dental pulp cells (DPCs), adherent cells derived from dental pulp tissues, are potential tools for cell transplantation therapy. However, little work has been done to optimize such transplantation. In this study, DPCs were treated with fibroblast growth factor-2 (FGF2) for 5–6 consecutive serial passages and were transplanted into the injury site immediately after complete transection of the rat spinal cord. FGF2 priming facilitated the DPCs to promote axonal regeneration and to improve locomotor functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Some axonal regeneration and locomotor recovery were observed. 198 In vitro, astrocytes were transfected to overexpress nerve growth factor (NGF) and encapsulated into a collagen scaffold. They were then added to rat dorsal root ganglion culture and found to significantly enhance axonal growth.…”
Section: Reproduced Withmentioning
confidence: 99%
“…Some axonal regeneration and locomotor recovery were observed. 198 In vitro, astrocytes were transfected to overexpress nerve growth factor (NGF) and encapsulated into a collagen scaffold. They were then added to rat dorsal root ganglion culture and found to significantly enhance axonal growth.…”
Section: Reproduced Withmentioning
confidence: 99%
“…Additionally, a recent study showed that injection of DPCs into rat spinal cord injury significantly improved axon regeneration and functional recovery, and this effect was further enhanced when the DPCs were cultured with fibroblast growth factor 2 (FGF2). 31 Therefore, engineering a method to deliver DPCs to a site of PNI could be an effective means of sustained NTF delivery, and priming DPCs with FGF2 may enhance the bioactivity of these cells for use in regenerative peripheral nerve therapies.…”
Section: Introductionmentioning
confidence: 99%
“…7 The microenvironment of the spinal cord changes immediately after a mechanical crushing or stretching of the spinal cord. [8][9][10] Axonal damage and cell membrane disruption cause glia loss in the primary injury of the spinal cord. 11 Then, a cascade of molecular and signaling pathways initiate a series of secondary injuries to the spinal cord.…”
Section: Introductionmentioning
confidence: 99%